Pengaruh Gaya Kepemimpinan Otokratik dan Kepuasan Kerja terhadap Kinerja Karyawan PT. Borwita Citra Prima-Bukalapak Cikarang - Mohamad Nur Husein Zailani; M. Amirudin; Asep Maulana (Universitas Batanghari, 2022)
Problems related to PT. Borwita Citra Prima – Bukalapak Cikarang who has problems regarding employee performance in the distribution process of goods which so far is considered to be still unstable and there are frequent complaints from consumers regarding the delivery of goods both in terms of time and quality of goods, causing a rejection of the distribution process of these goods, the following is a table of the process of shipping goods at PT. Borwita Citra Prima – Bukalapak Cikarang. This study aims to determine the effect of autocratic leadership style and job satisfaction on the performance of employees of PT. Borwita Citra Prima – Bukalapak Cikarang The research method used in this research is descriptive method. The technique of collecting data is through primary data, namely data obtained directly by using questionnaires distributed. This study used 80 samples of employees of PT. Borwita Citra Prima – Bukalapak Cikarang and using descriptive analysis methods, calculating respondents' responses, and testing hypotheses using t-test and f-test and coefficient of determination analysis. and significant to the performance of employees at PT. Borwita Citra Prima – Bukalapak Cikarang.